Spatio-temporal analyses of fruit fly populations in selected areas of the Western Cape - Bekker, Gerard Francois Hermanus van Ginkel (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDConsEcol)--Stellenbosch University, 2019.